ШЛЯХИ ПІДВИЩЕННЯ ПРОФЕСІОНАЛІЗМУ ПЕДАГОГІЧНИХ КАДРІВ (Педагогіка вищої та середньої школи, 2022)
The article is devoted to the issue of improving the professional skills of the pedagogical staff, where a person and it’s (his or her) own potential is of particular importance. The ways of improvement are presented in the article.